Burden of pertussis among young infants in Malaysia: A hospital-based surveillance study. Issue 35 (19th August 2022) - Mohamed, Thahira J.; Fong, Siew M.; Nadarajaw, Thiyagar; Choo, Chong M.; Yusoff, Nik Khairulddin Nik; Nachiappan, Jeyaseelan P.; Chan, Kwai Cheng; Koh, M.T.; Amran, Fairuz; Hashim, Rohaidah; Jabar, Kartini A.; Teh, Cindy Shuan Ju; et al.
Abstract: Background: The case fatality rate and the risk of complications due to pertussis is very high in infants. Asia has the second highest childhood pertussis burden. The study aimed to assess the prevalence, clinical complications, and mortality rates of pertussis disease requiring hospitalization among young infants in Malaysia. Methods: The study was a one-year, hospital-based, multi-site surveillance of infants less than six months of age with symptoms consistent with pertussis and a cross-sectional analysis of their mothers for recent pertussis infection. Information was obtained from medical records and interviews with the parents. Pertussis diagnosis was confirmed for all infants through serum anti-PT titration test or PCR test. Results: 441 possible cases of pertussis were included in this study. Of these, 12.7 % had laboratory confirmation of pertussis. Infants with confirmed pertussis had significantly higher rates of cyanosis (37.5 % vs 8.6 %; p < 0.0001) and apnea (12.5 % vs 3.9 %; p = 0.027) than test-negative infants. Most infants from both groups were in recovery/recovered at discharge. Those with confirmed pertussis had higher case fatality rate than test-negative cases (5.4 % vs 1.0 %; p = 0.094), but the difference did not reach significance. The majority of confirmed pertussis cases (89.3 %) occurred in infants too young to be fully vaccinated or under-vaccinated for their age. Both test-negative and confirmed pertussis resulted in work-day losses and incurred costs for both parents. Conclusions: A high pertussis disease burden persists in infants less than six months of age, especially among those un- and under-vaccinated. Maternal and complete, on-time infant vaccination is important to reduce disease burden.